Investigating glyoxylate-mediated transamination using dipeptide arrays and proteomic peptide mixtures - Tan, Xiaohong (2020)
Glyoxylate-mediated transamination (GT) is a classic, potentially general, and N-terminus-specific protein modification method useful for the preparation of bioconjugates. However, there is a lack of information on whether and how readily a particular N-terminal amino acid (in the context of a peptide chain) can be converted to the 2-oxoacyl moiety under GT conditions. Here, we conducted a systematic investigation of GT using membrane-bound dipeptide arrays that include all the 400 possible dipeptide combinations of the 20 genetically encoded amino acids. This colorimetric method offers a convenient way to assess the GT reaction tendency of N-terminal residues by the naked eye. It also provides interesting information about the effect of the second residues on GT, which has not been reported previously. In addition, we also designed a proteomics approach to study GT in solution using tryptic peptide mixtures, which not only confirmed many of our findings in peptide array assays but also revealed potential side reaction products. Taken together, our studies will make the future use of GT for protein modification in a much more predictable way.